(untitled) (TEL Tempo, Espaço e Linguagem, 2022)
This article intends to tension a debate about one of the results obtained through a qualitative master’s research that analyzed the perceptions of authority of beginning teachers who work in public high schools and their relations with gender. Seven teachers who work in high school and public education in Minas Gerais were interviewed. Among the research results, it was found that the teacher’s race factor can also influence the legitimacy of the teaching authority.